The Study of Porosity and Photoluminescence Properties of Nanoporous Silicon Layer Under Anodization Current Density Formation by Double Tank Electrochemical Etching Cell - Narin Atiwongsangthong (My University, 2021)
This research presents the effect of the constant current density on nanoporous silicon formation by double tank electrochemical etching cell without coating aluminum on the backside of silicon wafer. In this paper, the constant current density is increased from 10 mA/cm 2 to 25 mA/cm 2 during the anodization process by using hydrofluoric acid and ethanol at ratio 4:1 and the etching time are 10 minute. Gravimetric and Photoluminescence measurement were performed to investigate the porosity and the uniform distribution of nanoporous silicon layer respectively. The result shows that the porosity of nanoporous silicon layer was increased when the constant current density increased. The range of the porosity 46% to 80% and it is dependent on constant current density. The photoluminescence measurement with irradiate ultraviolet light on the surface of samples it was observed that hight uniformity of photoluminescence intensity. Indicates that the nanoporous silicon surface are more uniform distribution. This research discovers that the constant current density has large effect on the porosity of nanoporous silicon layer. Results show good improvement the nanoporous silicon formation by double tank electrochemical etching cell without coating aluminum on the backside of silicon.
Keywords: Silicon Nanostructures and Photoluminescence; Nanowire Synthesis and Applications; Anodic Oxide Films and Nanostructures